How many risk factors are too many: massive pulmonary embolism in a patient with ulcerative colitis and steroid-induced vertebral fractures: a case report - Stanislav Georgiev; Lyuboslava Pampulova; Philip Abedinov; Rumen Iliev; Emil Hadzhiev; Dimitar Petkov (Pharmacia, 2026)
Pulmonary embolism (PE) is a serious and potentially fatal condition caused by obstruction of the pulmonary arterial system by thrombotic material. While the baseline risk in the general population remains low, it rises significantly in the presence of certain predisposing factors such as major surgery, malignancy, prolonged immobilization, and advanced age (Henke et al. 2020). Corticosteroid therapy increases the risk of venous thromboembolism (VTE) through both direct and indirect mechanisms. Directly, it induces a prothrombotic state by increasing procoagulant factors and suppressing fibrinolysis (Stuijver et al. 2013). Indirectly, long-term glucocorticoid (GCS) therapy causes secondary osteoporosis in 30–50% of patients, resulting in a 160% higher risk of vertebral fractures (Kobza et al. 2021). Major osteoporotic fractures are themselves independent risk factors for VTE (Ventrapragada et al. 2024). Furthermore, these fractures can lead to immobilization. Several underlying diseases and clinical conditions, such as chronic inflammatory diseases, significantly increase the risk of developing PE by promoting hypercoagulability, venous stasis, and endothelial injury, collectively known as Virchow’s triad (Shah et al. 2022). This case report describes a 41-year-old male patient who developed a massive pulmonary embolism shortly after neurosurgical intervention for multiple vertebral fractures. The fractures were associated with long-term corticosteroid therapy for ulcerative colitis. The patient required urgent embolectomy. This case highlights the importance of identifying risk factors associated with an increased incidence of pulmonary embolism, as this enables early detection of postoperative thromboembolic complications and prompt management, ultimately improving outcomes.